(untitled) (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
The plasma cell leukemia (PCL) is an extremely uncommon malignant blood disorder with a pejorative prognosis. It is defined by the presence of at least 20% of plasma cells in the peripheral blood or an absolute number of circulating plasma cells greater than 2 G /L. It appears under two variants: secondary PCL that complicates known multiple myeloma and primitive PCL that is immediately leukemic. We report the case of a 56 years old male patient who presented 2 months before his hospitalization diffuse bone pains with asthenia. The CBC revealed an anemia and a leukocytosis. The blood smear objectified 3 G/L circulating plasma cells. The bone marrow exam noted a rich cellularity and a marrow invaded up to 60% by dystrophic plasma cells. The clinical presentation of the plasma cell leukemia, its cytological smear characteristics, immunophenotypical, pathophysiological, therapeutic approach and outcome will be reminded in this article.